Dispute of Former Building Use Rights Decision Number 2204 K/Pdt/2018/PN Smg - Narendra, Bagas Putra; Putri, Sarah Hasnanda; Mulia, Sheilla Siartha (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the dispute over the former Building Use Rights (HGB) Decisions 2204 K/Pdt/2018/PN Smg, by analyzing how the status of former HGB land is disputed and the legal consequences of the expiration of HGB and the steps that can be taken so that the certificate remains valid. This research is a normative research. Where the normative juridical approach is research that uses library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials as the main legal materials. Research result showed that the court rejected the cassation request from the LANNE TEDJAWINATA Cassation Petitioner, and punished the Cassation Petitioner to pay court fees at this level of cassation in the amount of Rp. 500,000.00 (five hundred thousand rupiahs). On the basis of this decision, the control over the object of dispute by the defendants is not an act against the law, because the land of the object of dispute is state land controlled by the defendants. The legal consequences of a dispute over a former HGB within a certain period of time is that the right to lose its rights due to expiration, i.e. if the party who has controlled the land for a certain period of time and the land becomes state land, the party who controls the land can submit an application for the land to the agency which has the authority to fulfill the conditions determined by the applicable regulations in accordance with Presidential Decree No. 32 of 1979. Former Western land converted into HGB deadline for 20 years since UUPA, so that in 1980 HGB was expired and the land became state land.